PENGARUH PEMBELAJARAN TEMATIK KELAUTAN TERHADAP PENANAMAN KARAKTER KEBAHARIAN PADA ANAK USIA 5-6 TAHUN DI TK HANG TUAH 12 SURABAYA - Wardani, Candra (Jurnal Anak Usia Dini dan Pendidikan Anak Usia Dini, 2019)
ABSTRACT This study is to determine the effect of marine thematic learning on children aged 5-6 years at Hang Tuah 12 Kindergarten and explain the character of children aged 5-6 years at Hang Tuah 12 Surabaya Kindergarten before and after marine thematic learning so that from this learning applicable education can be applied with the marine environment in instilling a sense of marine love from an early age. Data collection techniques used in this study were observation and documentation. Data analysis in the study used the Wilcoxon Match Pairs Test to test the difference test of two related samples. This test involved a study population of group B TK Hang Tuah 12 Surabaya. Based on the results of data analysis that thematic marine learning has an influence in the cultivation of maritime character in children aged 5-6 years at kindergarten Hang Tuah 12 Surabaya. The results of data analysis obtained T count of 0 and T table of 16, because 0